Child Trafficking vs. Child Sexual Exploitation: Critical reflection on the UK media reports - Krsmanovic, Elena (Anti-Trafficking Review, 2021)
This article explores how UK media narratives construct sexual exploitation of British children as a phenomenon to be approached differently than sexual exploitation of trafficked minors who are non-British nationals. Qualitative analysis of media articles that frame infamous child sexual exploitation cases as occurrences of human trafficking shows that they bank on the motifs from the historical white slavery myth. Thereby, these articles endorse the stereotypes of white victim and foreign trafficker and obscure the diversity of trafficking victims, perpetrators, and experiences. Furthermore, comparison between media reports focusing on cases involving British minors, on the one hand, and minors from abroad, on the other hand, reveals that only the former problematise inadequate victim assistance and systemic failures in dealing with sexual exploitation of minors. This leaves structural causes of child trafficking unaddressed, promotes differential treatment of victims based on their nationality, and stigmatises whole communities as immoral and crime-prone.